The Megengan Tradition and Its Symbolic Meaning in the Social Construction Context During the Advent of Ramadan - Ifa Febyanti Nabiilah; Isa Anshori (Mimbar Agama dan Budaya, 2023)
Tradition, widely acknowledged as a custom rooted in ancient historical events, holds immense significance within societies, often serving diverse purposes ranging from political to cultural, depending on the historical context. Indonesia, a nation rich in cultural diversity, boasts a myriad of traditions unique to each region, with many communities steadfastly adhering to these age-old customs. This article endeavors to explore the enduring nature of traditions and their integral role in shaping human lives. It contends that traditions, developed over time, serve as repositories of cultural and historical identity, fostering a sense of belonging and continuity across generations. By delving into the intricacies of Indonesia's diverse cultural traditions, the article seeks to illuminate the dynamic interplay between tradition and societal evolution. Moreover, it emphasizes the imperative of preserving these traditions to ensure their proper development and transmission to future generations. In essence, the article aims to foster a comprehensive understanding of the profound impact of traditions on human life and the imperative of their preservation for the enrichment of cultural heritage.